Switchable semiconductor optical fiber laser incorporating AWG and broadband FBG with high SMSR - Ahmad, Harith; Zulkifli, Mohd Zamani; Thambiratnam, Kavintheran; Latiff, Anas Abdul; Harun, Sulaiman Wadi (IOP Publishing, 2009)
In this paper we propose and demonstrate a switchable wavelength fiber laser (SWFL) using a semiconductor optical amplifier (SOA) together with an arrayed waveguide grating (AWG). The proposed SOA-based SWFL is capable of generating up to 14 lasing channels from 1530.1 nm to 1534.9 nm at a channel spacing of 0.8 nm (100 GHz) and a bandwidth of 11.8 and 10.2 nm respectively. The EDFA-based SWFL has a higher peak power at -5 dBm, while to SOA-based SWFL has a peak power of only -10 dBm. However, the SOA-based SWFL exhibits a much better SMSR of between 10 to 20 dB as compared to the SMSR of the EDFA-based SWFL due to the inhomogeneous broadening properties of the SOA.